The Major Cause of Observed Erosion Surge on the Beaches North of Dar Es Salaam City - Nyandwi, N. (Tanzania Journal of Science, 2021)
Surges in coastal erosion north of Dar es Salaam city have been documented from 1977 to the early 1980s and around 1997/98. Analysis of the wind data shows that the documented increase in coastal erosion coincided with increased wind speeds. Extreme winds in excess of 10-11 m s-1 were experienced during 1976-78, 1984 and after 1996. Their coincidence with extreme high tides produced the high erosion rates. Using beach profile data for the years 1998-2000 the evolution of the beach profile with the changing monsoon winds and sediment input by rivers could be demonstrated. The beach erosion took place during the Southeast Monsoon when the alongshore sediment transport is northwards. During the Northeast Monsoon, the reversed transport is smaller to rebuild the beach. In this study incipient seaward shoreline shift was observed towards the end of the 1999 SE monsoon period and subsequent monitoring revealed a seaward shift by the end of the next NE monsoon. The shift of the shoreline was attributed to a redistribution of the large volumes of fluvial sand that was supplied during the El-Nino rains of April/May 1998. With the drop in annual wind strengths, coastal erosion has since stabilized.